Assessment of genetic diversity among 32 pigeon pea genotypes using morphological traits and simple sequence repeat markers in Northern Ghana - Addae-Frimpomaah, F.; Denwar, N. N.; Adazebra, G. A.; Adjebeng-Danquah, J.; Kanton, R. A. L.; Afful, N. T.; Duut, M. (International Journal of Agricultural Technology, 2021)
Thirty-two pigeon pea (Cajanus cajan) genotypes comprising of 26 exotic genotypes and six landraces were characterised with morphological and molecular markers to assess the extent of inherent genetic variability and agronomic performance in the Guinea Savannah ecology of northern Ghana. Twenty morphological traits (10 qualitative and 10 quantitative) and alongside 10 simple sequence repeat (SSR) markers were used for the characterisation. Result indicated highly statistical significant (p < 0.001) genotypic differences for ten quantitative traits. Grain yield ranged between 501.30 kg and 1280.00 kg with a mean of 653.32 kg. Pearson correlation analysis revealed the strongest character association (r = 0.99) between days to 50 % flowering (DFPF) and days to pod initiation (DPI) implying these traits can be selected together. Principal component analyses of the morphological traits revealed the first three principal components (PC’s) accounting for 87.87% of the total variation with all the traits being captured by PC2, apart from 100 seed weight. A total of 15 alleles with a range of 2 to 3 and a mean of 2.5 alleles per marker were generated from six polymorphic markers out of the 10 SSR markers tested. Polymorphic information content (PIC) ranged from 0.11 to 0.37 with mean of 0.25 for the six polymorphic markers. A dendrogram derived from Jaccard coefficient analysis of the morphological traits revealed two main clusters at 0.6 similarity level whilst for the molecular markers, four main clusters were obtained at 0.6 similarity level. Genotype ICEAP 00673-1 formed a solitary cluster based on both morphological and molecular data indicating its uniqueness at both levels of classification. The study revealed ample genetic diversity within the germplasm to warrant selection for further improvement in the breeding programme